Sistem Pendeteksi Atrial Fibrilasi Berdasarkan Fitur Mean, Median, Standar Deviasi, Min, dan Maks Interval RR menggunakan Metode K-NN - Hani Firdhausyah; Rizal Maulana; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
91% of sudden deaths in Indonesia are due to Arrhythmias. Atrial Fibrillation is one type of arrhythmia that occurs most often among other types. Atrial fibrillation is characterized by an irregular heartbeat due to abnormal electrical activity. Blood collects in the atria and is not supplied to the ventricles sufficiently. So that the heart fails to pump enough blood to the lungs. For the examination, it is quite expensive, especially in the hospital. Therefore a system was developed to be able to detect AF without injuring the body. The system consists of several functions, namely the ECG signal generator using the AD8232 sensor, data processing using the Arduino Nano board, and displaying the classification or diagnosis results of the class